Prevalence of COL4A1 and COL4A2 mutations in severe fetal multifocal hemorrhagic and/or ischemic cerebral lesions. (3rd May 2021) - Maurice, P.; Guilbaud, L.; Garel, J.; Mine, M.; Dugas, A.; Friszer, S.; Maisonneuve, E.; Moutard, M.‐L.; Coste, T.; Héron, D.; Tournier‐Lasserve, E.; Garel, C.; et al.
ABSTRACT: Objective: To establish the prevalence of COL4A1 and COL4A2 gene mutations in fetuses presenting with a phenotype suggestive of cerebral injury. Methods: This was a single‐center retrospective analysis of all cases of fetal cerebral anomalies suggestive of COL4A1 or COL4A2 gene mutation over the period 2009–2018. Inclusion criteria were: (1) severe and/or multifocal hemorrhagic cerebral lesions; (2) multifocal ischemic‐hemorrhagic cerebral lesions. These anomalies could be of different ages and associated with schizencephaly or porencephaly. Between fetuses with and those without a mutation, we compared gestational age at the time of diagnosis, parity and fetal gender. Results: Among the 956 cases of cerebral anomaly diagnosed in our center during the 10‐year study period, 18 fetuses were identified for inclusion. A pathogenic COL4A1 gene mutation was found in five of these cases, among which four were de‐novo mutations. A variant of unknown significance was found in four fetuses: in the COL4A1 gene in one case and in the COL4A2 gene in three cases. No COL4A1 or COL4A2 mutation was found in the remaining nine fetuses. The median (interquartile range) gestational age at diagnosis was significantly lower in cases with a mutation (24 (22–26) weeks) than in cases without a mutation (32 (29.5–34.5) weeks) ( P = 0.03). Conclusions: A phenotype suggestive of cerebral injury was found in 18 of the 956 (1.9%) cases in our population, in 28% of which there was an associated COL4A1 or COL4A2 mutation. COL4A1 and COL4A2 gene mutations should be sought systematically in cases of severe and/or multifocal hemorrhagic or ischemic‐hemorrhagic cerebral lesions, with or without schizencephaly or porencephaly. © 2020 International Society of Ultrasound in Obstetrics and Gynecology.